Comprehensive doping scheme for MOSFETs in ultra-low-power subthreshold circuits design. (June 2016) - Hossain, Munem; Chowdhury, Masud H.
Abstract: Devices for subthreshold circuits do not require halo and retrograde doping like conventional super-threshold devices. This will reduce the number of steps in the fabrication process, parasitic capacitance and substrate noise dramatically in the subthreshold devices. This paper introduces a new comprehensive doping scheme for the transistors in subthreshold circuits. The proposed doping scheme would bring doping changes in the source and drain areas along with the substrate and channel regions of the transistors. The proposed doping scheme is characterized by the absence of halos at the source and drain ends. We propose a Gaussian doping distribution inside the source and drain regions, and a low–high–low distribution across the depth of the transistor from the channel surface towards the body region. It also has a low–high–low doping distribution along the length of the transistor below the channel region. Results show that the optimized device with the proposed doping profiles would provide higher ON current ( I on ) at smaller body bias condition. The analysis is performed by changing the doping profile, the body bias, and the gate–source voltage ( V gs ) to observe the off-state current ( I off ), threshold voltage variation, magnitude of I on /I off ratio, transconductance, and the output conductance with the proposed doping profiles.